(untitled) (BIRDEM Medical Journal, 2025)
Endometriosis is growing of endometrial cells in places other than normal uterine cavity. Endometriosis commonly affects ovaries and fallopian tubes. But it can occur anywhere in the body. Rarely it can develop within the abdominal wall. Abdominal wall endometriosis may happen after Caesarean section or any other pelvic surgery. Patients mainly present with abdominal pain. We are reporting 3 cases of abdominal endometriosis. They had history of lower segment Caesarean sections. They had pain and palpable lumps in the site of previous surgical scars during menstruation. Among the 3 cases, 1 patient underwent surgery and other 2 patients refused to do surgery. Orally Dienogest was administered to those 2 patients. All of them were improved. Scar endometriosis is not very common. There are medical and surgical options of management, among which surgery is more preferred. It can be diagnosed radiologically. Preventive methods should be undertaken to avoid endometrial tissue implantation which leads to scar endometriosis. BIRDEM Med J 2025; 15(2): 86-89